CLINICAL AND DIAGNOSTIC VALUE OF DETERMINATION OF NEOPTERIN IN ATOPIC DERMATITIS IN CHILDREN - M. M. BEN; E. YU. YANCHEVSKAYA; O. A. MESNYANKINA (Кубанский научный медицинский вестник, 2018)
Aim. To improve the diagnosis of allergic skin diseases in childrenMaterials and methods. 135 children aged from 2 to 6 with atopic dermatitis were examined during exacerbation. They were on inpatient treatment in the skin and venereologic department of the Regional skin and venereologic dispensary and the Department of Allergology of the Regional children's clinical hospital. At the same time, 103 people (the main group) had uncomplicated course of the disease, 32 patients had complications of atopic dermatitis in the form of secondary infection. The control group consisted of 29 children aged 2 to 6. Neopterin in serum was determined by enzyme-linked immunosorbent analysis using test kits "Neopterin ELISA" (Germany). Statistical reliability of the obtained data was evaluated using The Student's test.Results. Atopic dermatitis in children, regardless of clinical manifestations, is accompanied by an increase in the content of neopterin in serum. The nature of the increase in the level of neopterin is determined by the duration of the disease, while its highest values are characteristic of the prolonged course of the process (over 4 years).Conclusion. The determination of neopterin in children with atopic dermatitis is a promising laboratory method for assessing the severity of dermatosis, monitoring and forecasting the further course of the process, as well as evaluating the effectiveness of therapeutic measures.